2009
DOI: 10.1530/eje-08-0911
|View full text |Cite
|
Sign up to set email alerts
|

Presence of pituitary adenylate cyclase activating polypeptide-38 in human plasma and milk

Abstract: Objective: Pituitary adenylate cyclase activating polypeptide (PACAP) is a pleiotropic and multifunctional neuropeptide widely distributed throughout the body. It is involved in the regulation of various physiological and pathophysiological processes, such as reproduction, thermoregulation, motor activity, brain development, neuronal survival, inflammation and pain. Since little is known about its distribution in humans, our aim was to examine PACAP-38 in human plasma. Furthermore, based on the presence of vas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 15 publications
2
32
0
Order By: Relevance
“…However, in the second and third trimester of pregnancy and during lactation a signifi cant elevation could be observed compared to the earlier gestational period and nonpregnant healthy volunteers [ 20 , 21 ]. We detected 5-to 20-fold higher concentration of PACAP38 in the milk whey compared to the respective plasma samples [ 20 ]. Similarly to our results numerous studies measured higher concentration of bioactive factors in the milk than in the plasma.…”
Section: Abstract Pacap-like Immunoreactivity • Milk • Lactation • Masupporting
confidence: 89%
“…However, in the second and third trimester of pregnancy and during lactation a signifi cant elevation could be observed compared to the earlier gestational period and nonpregnant healthy volunteers [ 20 , 21 ]. We detected 5-to 20-fold higher concentration of PACAP38 in the milk whey compared to the respective plasma samples [ 20 ]. Similarly to our results numerous studies measured higher concentration of bioactive factors in the milk than in the plasma.…”
Section: Abstract Pacap-like Immunoreactivity • Milk • Lactation • Masupporting
confidence: 89%
“…These results show that an altered or bound form of the peptide was present in the amniotic fl uid, the signifi cance of which still awaits further investigation. PACAP levels were markedly higher in the breast milk than in the plasma [ 30 ]. This topic is reviewed in a separate chapter (Chap.…”
Section: Pregnancy and Deliverymentioning
confidence: 99%
“…6,7,11 Moreover, Borzsei et al reported PACAP38 is present in human plasma. 57 Considering these reports, the source of endogenous PACAP present could be a neuron or derived from the plasma. Cardiomyocytes could also be the primary source, like their production of ANP, although there is no data to definitively support this concept.…”
Section: Pacap and Heart Diseasementioning
confidence: 99%